Podargus brachypterus vs. macrorhynchus: misuse of Article 32.5.1.1 of the Code - Schodde, Richard (Zootaxa, 2009)
Dickinson et al. (2009) argued that the in-use name brachypterus Gould, 1841 for the western Australian subspecies of the Tawny Frogmouth (Aves: Podargus strigoides) must be replaced by macrorhynchus Gould, 1841. The latter was an alternative but unused name published for the frogmouth in the same paper (Gould 1841). In justifying their action, Dickinson et al. (2009) pointed out that brachypterus had been “erased” in a corrigendum to the paper. Then, resting their case on Art. 32.5.1.1 of the International Code of Zoological Nomenclature (ICZN 1999), hereafter the Code, they went on to assume that such a correction was “clear evidence” that brachypterus was “an inadvertent error” in spelling. Therefore, they concluded, macrorhynchus was the “correct original spelling”.